Slow and Steady: A Systematic Review of ICU Care Models Relevant to Pediatric Chronic Critical Illness - Troch, Rachel; Schwartz, Jamie; Boss, Renee (Journal of Pediatric Intensive Care, 2020)
There is a growing population of children with prolonged intensive care unit (ICU) hospitalization. These children with chronic critical illness (CCI) have a high health care utilization. Emerging data suggest a mismatch between the ICU acute care models and the daily care needs of these patients. Clinicians and parents report that the frequent treatment alterations typical for ICU care may be interrupting and jeopardizing the slow recoveries typical for children with CCI. These frequent treatment titrations could therefore be prolonging ICU stays even further. The aim of this study is to evaluate and summarize existing literature regarding pace and consistency of ICU care for patients with CCI. We performed a systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines (of September 2018). PubMed (biomedical and life sciences literature), Excerpta Medica database (EMBASE), and The Cumulative Index to Nursing and Allied Health Literature (CINAHL) were searched for English-language studies with data about CCI, care models, and pacing of clinical management. Four unique papers were identified. Our most important finding was that quality data on chronic ICU management, particularly for children, is sparse. All papers in this review confirmed the unique needs of chronic patients, particularly related to respiratory management, which is a common driver of ICU length of stay. Taken together, the papers support the hypothesis that protocols to reduce interdisciplinary management variability and to allow for slower management pacing should be studied for their impact on patient and health system outcomes. Optimizing value in ICU care requires mapping of resources to patient needs, particularly for patients with the most intense resource utilization. For children with CCI, parents and clinicians report that rapid treatment changes undermine recovery and prolong ICU stays. This review highlights the lack of quality pediatric research in this area and supports further investigation of a “slow and steady” approach to ICU management for children with CCI.
Keywords: chronic critical illness; intensive care; multidisciplinary; protocol; pathway